Electric-field-induced Shift in the Threshold Voltage in LaAlO3/SrTiO3 Heterostructures - Kim, Seong Keun; Kim, Shin-Ik; Lim, Hyungkwang; Jeong, Doo Seok; Kwon, Beomjin; Baek, Seung-Hyub; Kim, Jin-Sang (NATURE PUBLISHING GROUP, 2015)
The two-dimensional electron gas (2DEG) at the interface between insulating LaAlO3 and SrTiO3 is intriguing both as a fundamental science topic and for possible applications in electronics or sensors. For example, because the electrical conductance of the 2DEG at the LaAlO3/SrTiO(3)Z interface can be tuned by applying an electric field, new electronic devices utilizing the 2DEG at the LaAlO3/SrTiO3 interface could be possible. For the implementation of field-effect devices utilizing the 2DEG, determining the on/off switching voltage for the devices and ensuring their stability are essential. However, the factors influencing the threshold voltage have not been extensively investigated. Here, we report the voltage-induced shift of the threshold voltage of Pt/LaAlO3/SrTiO3 heterostructures. A large negative voltage induces an irreversible positive shift in the threshold voltage. In fact, after the application of such a large negative voltage, the original threshold voltage cannot be recovered even by application of a large positive electric field. This irreversibility is attributed to the generation of deep traps near the LaAlO3/SrTiO3 interface under the negative voltage. This finding could contribute to the implementation of nanoelectronic devices using the 2DEG at the LaAlO3/SrTiO3 interface.
Keywords: INTERFACE; GAS; CONDUCTIVITY; SURFACE